Developing the Ability to Add Integer through Live Worksheets among Grade II Pupils with Autism in Mathematics Learning - Suprihatin, S.; Yufitriani, Y.; Mulyeni, Trisna (Universitas Pendidikan Indonesia (UPI), 2024)
This paper presents a study using live worksheets to improve the capability of adding integer numbers in math subjects of pupils with autism. This study was classroom action research conducted in two cycles. The 1st cycle consists of 8 meetings and the 2nd cycle consists of 7 meetings, consisting of planning, action observation, and reflection. The data used is qualitative which is analyzed using thematic analyses and quantitative which is analyzed using simple quantitative data analysis. The result of this research showed that the average student's initial abilities or score was 47.5. After being given intervention in the first cycle the score becomes 62. This improvement occurs in the aspect of understanding the steps for adding integers to a maximum of 10 but has not yet reached the final step so the addition result is not correct. After being given intervention in cycle II, the average score increased to 93. In cycle II, the students were able to calculate the addition of integers correctly to a maximum result of 10 by following the steps provided on the live worksheets. Based on this data, it can be stated that live worksheets can improve the ability to add integer numbers with a maximum result of 10 in the 2nd grade of pupils with autism in this school.